Partisipasi Mendukung Anak Yatim dengan Kompetisi Olimpiade Al-Qur’an dan Matematika - Keisha Farellia Putri Lindra; Rahayu Mardikaningsih; Mirza Elmy Safira; Uswatun Chasanah; Didit Darmawan; Muhammad Yusron Maulana El-Yunusi; Sifa Fauzi Yulianis (Lembaga Pengembangan Kinerja Dosen, 2024)
Orphans often face obstacles in obtaining proper education. This program provides support through scholarships and participation in Qur'anic and Mathematics Olympiad competitions. Through this program, orphans can access quality education, increase their confidence, and develop their potential. The community service method was conducted through observation and documentation. The results show an increase in academic achievement and moral character development of the orphans. In conclusion, this program plays an important role in supporting orphans in achieving their right to education and developing their potential through educational competitions. The results show an increase in academic achievement, moral character development, and increased confidence of the orphans. This community service makes a positive contribution in supporting orphans in achieving their right to education and developing their potential through educational competitions.